Estonian Dental Students' Oral Health-Related Knowledge, Attitudes and Behaviours (KAB): National Survey-Based Study - Riad, Abanoub; Põld, Ave; Olak, Jana; Howaldt, Hans-Peter; Klugar, Miloslav; Krsek, Martin; Attia, Sameh (International journal of environmental research and public health, 2022)
The strategic plan for dentistry and oral health in Estonia of 2030 focuses on oral health promotion and disease prevention through undergraduate dental curricula and fostering public health-oriented research among students. The present study was designed as a descriptive cross-sectional study to evaluate oral health-related knowledge, attitudes, and behaviours (KAB) of dental students in Estonia. The study was carried out in the spring semester of 2020, and it used a modified version of the Hiroshima University Dental Behavioural Inventory (HU-DBI). A total of 129 students responded to the survey, constituting a response rate of 93.5% due to the total population sampling (census) technique used in this study and the small target population size. Out of the 124 students included in the final analysis, 79% were females, 62.1% were clinical students, 11.3% reported smoking tobacco at least once a week, and 86.3% reported problematic internet use. The present study found that mean HU-DBI score of Estonian dental students was 8.09 ± 1.22 which is so far the highest recorded HU-DBI score in Europe. There was no significant difference between female vs. male or preclinical vs. clinical students in terms of HU-DBI score. While clinical students reported less faulty oral hygiene practices, such as hard toothbrush use and aggressive toothbrushing, preclinical students reported a slightly higher mean HU-DBI score. Smoking behaviour was more common among male and clinical students, and it was also associated with alcohol drinking and worry about teeth colour and halitosis.
Keywords: Cross-Sectional Studies; Health Behavior; Male; practice; studenti stomatologie; Students, Dental; Health Knowledge, Attitudes, Practice; oral health; zdravé chování; oral hygiene; attitudes; Estonsko; Oral Hygiene; mužské pohlaví; orální hygiena; health knowledge; orální zdraví; průzkumy a dotazníky; Oral Health; Hiroshima University Dental Behavioural Inventory; lidé; ženské pohlaví; zdraví - znalosti, postoje, praxe; Humans; Estonia; dental students; dental education; průřezové studie; Female; Surveys and Questionnaires; HU-DBI